(untitled) - Clements, Andrew; 1949- (New York, 2002)
When fifteen-year-old Bobby wakes up and finds himself invisible, he and his parents and his new blind friend Alicia try to find out what caused his condition and how to reverse it.
Keywords: Fiction; Blind; Fiction; People with disabilities; Fiction